2009
DOI: 10.4196/kjpp.2009.13.5.393
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of G Proteins, Ca2+, and K+ Channels on Electrical Field Stimulation in Cat Esophageal Smooth Muscle

Abstract: NO released by myenteric neurons controls the off contraction induced by electrical field stimulation (EFS) in distal esophageal smooth muscle, but in the presence of nitric oxide synthase (NOS) inhibitor, L-NAME, contraction by EFS occurs at the same time. The authors investigated the intracellular signaling pathways related with G protein and ionic channel EFS-induced contraction using cat esophageal muscles. EFS-induced contractions were significantly suppressed by tetrodotoxin (1 μM) and atropine (1 μM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Muscle contractions were recorded using an isometric force transducer. Low-frequency EFS induced only off contraction but induced on contraction in the presence of N G -nitro-L-arginine methyl ester, suggesting that NO acts as an inhibitory mediator in smooth muscle [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle contractions were recorded using an isometric force transducer. Low-frequency EFS induced only off contraction but induced on contraction in the presence of N G -nitro-L-arginine methyl ester, suggesting that NO acts as an inhibitory mediator in smooth muscle [3].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of human esophageal strips using direct activation of enteric motor neurons by electrical field stimulation (EFS) have shown that lower esophageal smooth muscle relaxation is mainly caused by NO released from inhibitory enteric motor neurons, whereas esophageal contraction is mainly caused by acetylcholine released from excitatory enteric motor neurons acting on muscarinic receptors located in the smooth muscle [3,[28][29][30]. Except for acetylcholine, other neurotransmitters influence EFS-induced contraction in esophageal smooth muscle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ion currents generated via 4-AP-sensitive voltage-dependent K + channels in muscle might participate in EFS-induced responses [12]. In addition, EFS-induced those responses can be mediated by the activations Gi or Gs proteins, and that L-type Ca 2+ channel may be activated by G-protein alpha subunits, indicating that K + and Ca 2+ channel involve in the depolarization of esophageal smooth muscle [13]. Thus, studies are required to characterize the physiological regulation of Ca 2+ channel and to investigate the effects of other K + channels on EFS-induced on and off contractions.…”
Section: Introductionmentioning
confidence: 99%
“…1a). It has been reported that EFS-induced contraction in smooth muscle is nerve origin and cholinergic nerves are also responsible for contractions [20]. Then, the response of rat ileal smooth muscle to FLX was investigated initially.…”
Section: Resultsmentioning
confidence: 99%
“…However, the contraction of ileum muscle in mouse is mediated through the 5-HT 3 receptor [19]. Since there is a communication network between serotonin in the gut and the brain and spinal cord, it is possible that the drugs that are used for the brain such as antidepressants could influence serotonergic receptors in the GI tract [20]. However, little information concerning the effect of FLX on GI tract is available.…”
Section: Introductionmentioning
confidence: 99%